Pelatihan Pencatatan Administrasi Bagi Kader di Posyandu Cempaka I - Andi Usmar; Fitri Nur Fazriyah; Ade Wahyudi (Journal of Empowerment Community, 2026)
The purpose of this activity is to improve the skills of PKK Posyandu Cempaka I cadres in Dusun Cidolog, Gunungcupu Village, Sindangkasih District, Ciamis Regency, particularly in preparing monthly reports, including correspondence, financial, and other administrative reports submitted to the Gunungcupu Village PKK Team. In practice, discrepancies often occur between manual and digital data. Therefore, basic administrative training was conducted for the Cempaka I cadres to minimize data inconsistencies through organized record management using a one-day hands-on practice method. The training focused on mastering basic manual administration by inputting all data based on alphabetical order of infants, toddlers, and elderly individuals. This activity consisted of several stages: the preparation stage (coordination with the Cempaka I cadre team), the training stage (delivery of administrative materials), and the evaluation stage (direct report-making practice). The results showed that all participants were able to understand and apply the materials in preparing monthly reports and managing Posyandu Cempaka I administrative records properly, neatly, and accountably. It is expected that this activity will serve as motivation for Posyandu cadres to continuously enhance their capacity and professionalism as high-quality community health volunteers.